Relationship between dynamic postural balance with jumping and sprinting performance in professional soccer players - Guzmán-Muñoz, Eduardo; Alarcón-Rivera, Miguel; Salazar-Orellana, Cristian; Toro-Carrillo, Andrés; Valdés-Badilla, Pablo; Nuñez-Espinosa, Cristian; Hernández–Martínez, Jordan; Yáñez-Sepúlveda, Rodrigo (My University, 2025)
Introduction: Soccer is a sport that requires complex physical and motor skills, with dynamic postural balance being a key component for sports performance. Objective: To determine the relationship between dynamic postural balance and performance in jumping and sprint tests in professional soccer players. Methodology: A cross-sectional observational study was conducted with 24 professional soccer players, assessing dynamic postural balance using the Y-balance test (YBT) and physical performance with linear, curved, and change-of-direction sprint and jump tests. Data were analyzed using Pearson correlations. Results: The results showed that dynamic postural balance, especially in the anterior and posterolateral directions of the YBT, is positively associated with better performance in the jumping, linear sprint, and curved sprint tests. However, no significant relationships were found with the change-of-direction sprint. Conclusions: It is concluded that dynamic postural balance plays a fundamental role in specific soccer skills, such as jumping and sprinting, which underlines the importance of including balance training in physical preparation programs for professional soccer players.
Relación entre el equilibrio postural dinámico con el rendimiento de salto y esprint en futbolistas profesionales
Keywords: football; jump; performance; postural control; sport; sprint